Analisis Kelayakan dan Potensi Pengembangan Ekowisata pada Kawasan Wisata Alam Egon di Desa Egon Kecamatan Waigete Kabupaten Sikka - Anastasia Rande; Maria M. E. Purnama; Fadlan Pramatana (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Efforts to utilize optimal resources can be made by developing tourism with the concept of ecotourism. This research aims to determine the development aspects and feasibility value of each aspect of developing tourist attractions in the Egon natural tourism area in Egon Village, Waigete District, Sikka Regency. The sampling method used in this research is the purposive sampling method. As for determining the number of research samples using the Slovin formula, the number of respondents obtained was 94 respondents. Data taken through direct observation includes visitor perception data on aspects of attractiveness, accessibility, accommodation, facilities and infrastructure, security, socio-economic environmental conditions. The research results show that the potential offered is the beauty of natural panoramas, tracking routes, and several types of interesting flora and fauna. The results of research into the feasibility of tourism potential include several criteria such as attractiveness 76.67%, accessibility 70.83%, accommodation 33.33%, facilities and infrastructure 30%, security 100%, socio-economic environmental conditions 60%. The total feasibility level for these 6 criteria is 61.80, so it can be concluded that the Egon Natural Tourism Area is not yet suitable for development as a tourist location.